Advanced soil mechanics - Das, Braja M., 1941- (Boca Raton : CRC Press, Taylor & Francis Group, CRC press is an imprint of the Taylor & Francis Group, an Informa Business, 2013)
'An upper level undergraduate and begging graduate-level textbook, this new edition of a bestseller includes new sections on the AASHRO Soil Classification System and Soil Compaction as well as along with several recently developed empirical relationships for estimation of maximum dry unit weight based on compaction energy. It covers the procedures to estimate stress and displacement based on the theory of elasticity for place strain and three-dimensional cases and solutions for the determination of vertical stress due to various loading conditions on Westergaard-type material have been added. Several new example problems have been added to every chapter'--
Soil aggregate, plasticity, and classification -- Stresses and strains : elastic equilibrium -- Stresses and displacements in a soil mass : two dimensional problems -- Stresses and displacements in a soil mass : three dimensional problems -- Pore water pressure due to undrained loading -- Permeability -- Seepage -- Consolidation -- Shear strength of soils -- Elastic settlement of shallow foundations -- Consolidation settlement of shallow foundations -- Appendix.
'A SPON Press Book.'
Includes bibliographical references and index.
Keywords: Soil mechanics -- Textbooks